The dynamism of communication technology adoption, market information and welfare: Evidence from Nile perch (Lates niloticus) fish market, Mwanza, Tanzania - Kitole, Felician; Lihawa, Robert; Sesabo , Jennifer; Shitima, Christina (Lakes & Reservioirs, 2024)
An article submitted to the Lake & Reservoirs Journal of 2024.